0190 Occupational exposure to crystalline silica and death from lung cancer: g-estimation of structural accelerated failure time models. (21st August 2017) - Picciotto, Sally; Brown, Daniel M; Neophytou, Andreas M; Gallagher, Lisa E; Eisen, Ellen E; Checkoway, Harvey; Costello, Sadie
Abstract : Background: Occupational exposure to crystalline silica has been linked to mortality risk for lung cancer. The healthy worker survivor effect may bias effect estimates downward unless special methods are used to adjust for employment status, time off work, and co-exposures. Unlike traditional regression, g-estimation adjusts correctly for such time-varying confounders. Methods: We applied g-estimation of structural accelerated failure time models to estimate the number of years of life that could have been saved for mortality from all natural causes and from lung cancer if exposure to crystalline silica had been prevented among 2342 white male workers in the diatomaceous earth industry (1942–2011). Exposures were lagged 17 years because exposure data were only available through 1994; this also accounts for disease latency. Analyses adjusted for calendar year, age, Latino ethnicity, smoking status, duration of employment in the diatomaceous earth industry and exposure to crystalline silica before entering follow-up, prior exposure to crystalline silica, prior cumulative exposure to dust and asbestos, time taken off work, and employment status. Results: If all workers had been unexposed to crystalline silica, we estimated that workers who died of natural causes would have survived, on average, 1.1 years longer (95% CI: 0.3, 2.3) overall. Workers who died from lung cancer would have survived an estimated average of 9.0 years longer (95% CI: 4.4, 16.2) if they had been unexposed. Conclusions: A ban on exposure to crystalline silica in this cohort would have resulted in longer survival for workers, particularly those who died of lung cancer.